Improve The Logical Reasoning Ability of Primary School Students by Using Video Learning Assistant Teaching - Zhouli Huang; Ying Zhou; Tommy Tanu Wijaya; Ke Yan (Journal on Education, 2021)
Under the current situation of epidemic prevention and control, to ensure the continuous progress of student learning, Chinese Ministry of Education put forward the initiative of "suspension of classes without suspension of school". Primary and secondary schools have adopted online learning at home for students to "open schools in the cloud. There is a big difference between online learning and classroom learning. In this process, problems such as increased teaching burden of teachers, lack of interaction between teachers and students, and students' lack of active learning are also exposed. Video learning are a new type of teaching resource. It can improve the efficiency of primary school mathematics teaching by using video learning reasonably. Based on the above analysis, the purpose of this research is to investigate the development of primary school students' logical reasoning ability through the use of video leanings for auxiliary teaching. The research method adopts the experimental method and is divided into the experimental class and control class. The subjects of the study were 72 students from a primary school in Indonesia. Experimental results show that video learning for auxiliary teaching can effectively develop students' logical reasoning ability.